Guide for the Preparation of National Action Plans for Youth Employment. - Rosas, Gianni (International Labour Office, 2008)
This Guide has been developed by the ILO to assist governments, employers' and workers' organizations as well as other relevant stakeholders such as youth groups in preparing National Action Plans on Youth Employment (NAPs).